Dependent Population and Second Demographic Dividend in Nepal: A Study of Active Senior Citizens - Bhusal, Durga (Tribhuvan University Journal, 2019)
This review paper aims to disseminate a viewpoint on natural ability of senior citizen from the alternative angle of traditional perspective to later life. Second career management is essential job in present day of the 21st century. It reviews the existing evidences on aptitude of later life where physical force in the body is not only the means of production recognizing the participation of senior people to their households, communities, and the development course. Supporting generation of the 21st century is progressively having problematic time due to constricted household economy to achieve their obligation of enhancing elderly member of their family. Nepal Labour Force Survey 2017/18 and Population Monograph of Nepal 2014 are utilized as main data sources along with different empirical studies for the explanation to get the target of the study. The crux of this article—later life can contribute the socio-economic development of nation through silver economy involving to the site of earnings to produce more than they consume –posits the alternative perspective to old age dependency.